Research progress on the properties and applications of magnesium phosphate cement - Fang, Bodong; Hu, Zhuojun; Shi, Tao; Liu, Yanming; Wang, Xian; Yang, Daping; Zhu, Kuai; Zhao, Xingyu; Zhao, Zhifang (Ceramics international, 2023)
Magnesium phosphate cement (MPC) is a new cementing material with great development potential and excellent properties. In addition to traditional cement, MPC also has the characteristics of ceramics, refractory materials, and biological materials. The MPC materials can be applied especially in architecture and other fields such as wall spraying, structure repair, solid waste curing, biomedical engineering, and 3D printing. Nowadays, MPC materials are being used in more updated, cutting-edge applications. This paper mainly summarizes the research progress of MPC in terms of material properties and applications in various fields in recent years, analyzes the research results of various scholars, and discusses the future research direction and current problems to be solved.